The Shank3Venus/Venus knock in mouse enables isoform-specific functional studies of Shank3a - Bouquier, Nathalie; Sakkaki, Sophie; Raynaud, Fabrice; Hemonnot-Girard, Anne-Laure; Seube, Vincent; Compan, Vincent; Bertaso, Federica; Perroy, Julie; Moutin, Enora (Frontiers in Neuroscience, 2022)
Shank3 is a scaffolding protein essential for the organization and function of the glutamatergic postsynapse. Monogenic mutations in SHANK3 gene are among the leading genetic causes of Autism Spectrum Disorders (ASD). The multiplicity of Shank3 isoforms seems to generate as much functional diversity and yet, there are no tools to study endogenous Shank3 proteins in an isoform-specific manner. In this study, we created a novel transgenic mouse line, the Shank3Venus/Venus knock-in mouse, which allows to monitor the endogenous expression of the major Shank3 isoform in the brain, the full-length Shank3a isoform. We show that the endogenous Venus-Shank3a protein is localized in spines, is mainly expressed in the striatum and hippocampus of the developing brain and also found in the cortex of adult brain. We show that Shank3Venus/+ and Shank3Venus/Venus mice have no behavioral deficiency. We further crossed Shank3Venus/Venus mice with Shank3DC/DC mice, a model of ASD, to track the Venus-tagged wild-type copy of Shank3a in physiological (Shank3Venus/+) and pathological (Shank3Venus/DC) conditions. We report a developmental delay in brain expression of the Venus-Shank3a isoform in Shank3Venus/DC mice, compared to Shank3Venus/+ control mice. Altogether, our results show that the Shank3Venus/Venus mouse line is a powerful tool to study endogenous Shank3a expression, in physiological conditions and in ASD.